ACCESS : accessible course construction for every students success - Mahaffey, Cat; Walden, Ashlyn C. (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2025)
ACCESS: Accessible Course Construction for Every Student's Success is a practical guide to digital course design that incorporates and exceeds current accessibility practices for disabled and non-disabled students in higher education. Today's rapid proliferation of online, blended, and hybrid learning systems has alerted college and university staff to unforeseen yet urgent lapses in accommodating students' various learning needs and preferences. This book offers a wealth of learning design and delivery strategies that meaningfully address the notions of accessibility that move beyond compliance with the Americans With Disabilities Act (ADA). Each chapter explores accessibility in a situated context, making this an ideal resource for instructional design students and professionals, learning scientists, disability support personnel, and faculty developing their own digital courses.
Keywords: Internet in higher education; Education, Higher -- Computer-assisted instruction; Distance education; EDUCATION / Distance Education & Learning; EDUCATION / Higher